A Metastase Clear Cell Papillary Renal Cell Carcinoma (ccpRCC): A Case Report - Octavian, Aditya Eka; Rahmadianto, Hajid; Nawangtantrini, Gita (Indonesian Journal of Cancer, 2025)
Introduction: Clear cell papillary renal cell carcinoma (ccpRCC) was recently identified, which acts like a benign tumor entity introduced by WHO in 2016. It shares morphologic features in both clear cells and papillary cells. It is characterized by its unique immunohistochemical, morphologic, and genetic features and indolent behavior with no reported recurrence or metastasis before. This paper presents a case of ccpRCC in adulthood with spinal metastasis.Case Presentation: A 16-year-old female patient presented to the urology polyclinic of Prof. Dr. Margono Soekarjo Hospital with an abdominal lump and hematuria. Subsequently, the patient underwent radical nephrectomy. Histopathological examination confirmed ccpRCC. After six months, the patient exhibited weakness in the lower extremities, sensory disturbances, and urinary retention. She was referred to the Neurology department, where physical examinations revealed paraplegia inferior and segmental hypoesthesia at the vertebrae T12 level. MRI examination showed signs of vertebral metastases. After receiving immediate treatment from the neurology department, the neurosurgery department scheduled the patient for a surgical procedure. The case was followed for eight months. Conclusions: ccpRCC is a benign kidney tumor exhibiting a combination of clear cell and papillary cell carcinoma characteristics. While patients with ccpRCC are typically asymptomatic, cases are presenting with symptoms such as hematuria. This case demonstrates the occurrence of hematogenic metastases in ccpRCC, highlighting the need for surgical intervention to preserve existing functionality